Análise de sobrevivência aplicada ao estudo da mortalidade de lambari-do-rabo-amarelo - Pereira, Geraldo Magela da Cruz; Emiliano, Paulo César; Ferraz, Renato Barbosa; Salaro, Ana Lúcia; Alves, Raphael Fernandes Soares (Acta Biológica Paranaense, 2018)
<htm>Análise de sobrevivência aplicada ao estudo da mortalidade de lambari-do-rabo-amarelo </htm>